Psychosocial risks experienced by international students in the security industry of New Zealand : a thesis presented in partial fulfilment of the requirements of the Master of Business Studies (specialisation in HRM), Massey University, Auckland, New Zealand - Arslan, Hafiz Syed Muhammad (Massey University, 2019)
Many international students in New Zealand are employed under non-standard work arrangements as part-time/casual security guards in the security industry. The literature on the experiences of international students indicates that they often work irregular schedules, are paid minimum wages and benefits, and tend to be exploited by employers due to their limited knowledge about employment rights. Similarly, the literature concerning work in the security industry worldwide suggests that security guards generally work under unsafe and hazardous working conditions and are provided with limited equipment and training, which tends to have negative repercussions for their psychosocial wellbeing. However, there is sparse literature at both the national and global level discussing the experiences of international students working as security guards in the security industry. Thus, the present research was designed to qualitatively explore the experiences of international students engaged in non-standard work arrangements in the security industry of New Zealand and investigate their psychosocial wellbeing. Seven international students working as casual security guards within the broader Auckland region were interviewed. Three main overarching themes were identified in the analysis. Theme 1 highlighted ‘accessibility issues’ identified as workers’ inaccessibility to adequate provisions such as Personal Protective Equipment (PPE), kitchen and toilet facilities, sufficient training, adequate income and benefits, regular working hours, and knowledge about employment rights; all of which had negative consequences for their wellbeing. Relatedly, theme 2 ‘threats to psychosocial wellbeing’ presented a picture of the vulnerability of international student security guards in the industry by illuminating their exposure to physical and psychosocial harm, such as physical abuse and racial harassment, during their work. Additional stressors due to this group’s extended engagement with both studies and part-time work were also explored. In theme 3, the ‘unprofessional practices’ of both international students and employers (subcontractors) in relation to New Zealand employment law were outlined. Here, sub-themes of exploitation and self-exploitation were further investigated. Overall these findings emphasised the need for vigorous policy initiatives focussed on improving the working standards of the security industry and wellbeing of international students working as security guards, through collaborative efforts on the part of the regulatory agencies, main- contractors and subcontractors.
Keywords: Police, Private; Private security services; New Zealand; Auckland; Students, Foreign; Employment; Mental health; Attitudes; international students; security guards; non-standard work arrangements